MENUJU PEMIKIRAN EKONOMI IDEAL: TINJAUAN FILOSOFIS DAN EMPIRIS (Fokus Ekonomi, 2011)
Neoclassical economic thought which is a development of classical economic thought that is usedin the world and use the positivism paradigm, unsuitable and fail to be applied to developingcountries including Indonesia. The ideal of economic thought from the philosophycal andempirical point of view as an alternative to neoclassical economics is institutional economics.Keywords : economic thought, philosophical, institutional economics